ANALISA PEMANFAATAN OBLIGASI KORPORASI SEBAGAI ALTERNATIF PEMBIAYAAN PROYEK SWASTA (STUDI KASUS PROYEK PEMBANGUNAN VILLA EUREKA TUBAN-BALI) - M. Umarul Hasani; Putu Gede Suranata; A.A. Rai Asmani K. (Program Studi Teknik Sipil, Fakultas Teknik dan Perencanaan, Universitas Warmadewa, 2017)
ABSTRACT One of the alternative financing projects that can be used is by issuing corporate bonds. Bonds experienced considerable progress as financial instruments in the period of 2000. Bonds were able to become one of the financing alternatives for projects and competitive against other sources of financing such as loans from conventional banks. One of the project issues is the delay in project financing is expected to be resolved by alternative financing through corporate bond issuance. Eureka Villa private project in this research will try to simulate its financing by using financing through corporate bond issuance. For this purpose, a financial feasibility analysis of the investment system will be conducted using funds from corporate bonds on villa operations. The principal amount of the bonds to be issued are IDR 80,000,000,000.00 with 7.5% coupon per annum payable every 6 months and redeem principal bonds with sinking fund each year over the life of the bonds of 10 years. Nominal investment receipts of IDR 16,000,000,000.00 or in lot units of 3200 lots carried out during the implementation of the project is 12 months assuming the receipt of investment funds 5 times every 3 months. Payment of interest coupon and principal redemption are payable after the villa commences operations on September 1, 2017 with annual payment of IDR 14,005,000,000.00. After calculating the NPV & IRR for the income and outcome of the villa with the source of the cost of the bonds obtained NPV = (-IDR 77,048,163,482.40 ) < 0 and IRR = 1.5 Ã— 10-13% < MARR 12%, then the investment plan of Corporate Bonds on the construction project Eureka Villa Tuban - Bali using the NPV method and the IRR method is recommended